THE INFLUENCE OF SOCIALIZATION, APPLICATION SYSTEM QUALITY, APPLICATION USAGE KNOWLEDGE, AND THE USE OF THE E-SAMSAT APPLICATION AS A MEDIATION VARIABLE ON MOTOR VEHICLE TAXPAYER COMPLIANCE (CASE STUDY IN BEKASI CITY) - Wilander, Jordy (Tax Accounting Applied Journal, 2023)
This research was conducted as a case study in Bekasi City because revenue receipts, especially in vehicle taxes and the number of motorized vehicle owners, have increased significantly in 2018-2022. The government made an innovation in the form of an online application called "E-SAMSAT," which aims to reduce the number of taxpayers who do not comply with their motorized vehicle obligations and make it easier for taxpayers to carry out their obligations without the need to come to the SAMSAT office. This study examines the effect of socialization, the quality of the application system, and the knowledge of using the application on motor vehicle taxpayer compliance mediated by using the E-Samsat application. This research uses quantitative methods. The population in this study is the number of registered motor vehicle taxpayers in Bekasi City. Sampling using the random sampling method and the number of samples determined as many as 99 samples with the Slovin formula. We collected data using an e-survey with a questionnaire. This study used linear regression analysis and PROCESS by Hayes with the IBM SPSS 26 application. These results showed that socialization, application system quality, and application usage knowledge significantly affected motor vehicle taxpayer compliance mediated by the use of the E-Samsat application.